Procesamiento Difuso de Imágenes: Filtro Difuso para Eliminar el Ruido Impulsivo - Betancourt Uscátegui, Álvaro; Mujica Ballesteros, Andrés Edwin; Tapias, Hernán (Ingeniería, 2002)
This paper describes the fundamentals on fuzzy logic signal processing, modelling of differents statistical noise distribution ( impulsive, gaussian), clasical filters and multipass filter implemented by the authors.